Curcuma Longa: The Dye as a Potential Indicator in Titrimetric Analysis - Ozabor, C . W .; Sadol, A . O . (Mediterranean Journal of Social Sciences, 2012)
Curcuma longa is the botanical name of a ginger plant belonging to the family of zingiberaceae. Itcontains a colourful condiment with a distinctive pungent flavour. The natural product (curcuma longa)has a pH range of 8 to 9. The quantitative evaluation gave a percentage yield of 15.2. On Thin-layerchromatographic analysis, the dye gave Rf(methanol) value as 0.83. The ultra-violet visible (UV) spectra ofthe dye also showed absorption of 480nm corresponding to the region of dyes. Infra-red (IR) spectra of thedye from methanol extract showed intense peaks at 3423.8, 2961.7, 1739.5 and 1380.9 corresponding toO-H stretching of alcohol, C-H stretching of methyl and methylene groups, C=O of amides stretching andC-H bending vibrations of methyl and methylene groups respectively. An extraction was conducted wherea colourful yellow dye was produced from powdery curcuma longa with methanol as solvent. The indicatorproperty of the extracted dye was investigated using methyl orange as a reference indicator. It wasobserved that the titrimetric end-points obtained for the dye present in curcuma longa comparedreasonably with those of methyl orange. I strongly recommend that the dye from curcuma longa can beused as alternative to methyl orange during titrimetric analysis.